Analysis of Governance, Leverage and Financial Distress Conditions on Earnings Management in the Banking Services Sector in Indonesia - Rama Nopiana, Puspita; Rusmiati Salvi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This research is motivated by the existence of information asymmetry and the tendency of investors to pay more attention to earnings information as a parameter of company performance, which will encourage management to manipulate earnings which is called earnings management. The purpose of this study was to identify the effect of governance, leverage and financial distress conditions on earnings management in companies listed on the Indonesia Stock Exchange (IDX) focused on the banking sector. The method used is a quantitative descriptive method, with 35 data samples from 5 companies that have met the research sample criteria in the banking services sector for the period 2013-2019. The results of this study were analyzed and processed by statistical tests showing that leverage has a positive and significant effect on earnings management,